2019
DOI: 10.3390/molecules24101900
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics and In Vitro Digestibility of Malic Acid-Treated Corn Starch with Different pH Conditions

Abstract: The objective of this study was to investigate the influence of pH value on the in vitro digestibility of malic acid-treated corn starch in relation to its structural properties. Varying pH values (1.5–8.5) of 2 M malic acid solution were combined with corn starch in a forced-air oven at 130 °C for 12 h. Using Fourier-transform infrared spectroscopy (FT-IR), carbonyl groups were detected in malic acid-treated corn starch, indicating cross-linking through esterification. As the pH value of malic acid-treated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Esterified starch is an important part of modified starch. After organic acid treatment, such as malic, tartaric, citric, and glutaric acid, starch can be more widely used in various industries according to its different properties (Ačkar et al., 2015; Akubor, 2013; Barczynska et al., 2019; Lee et al., 2019). However, l ‐malic acid is easily prepared by microbial fermentation or enzymatic conversion which has stereospecificity, and can be used as a pasta enhancer (Battat et al., 1991; Iyyappan et al., 2019; Moon et al., 2008; Neufeid et al., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Esterified starch is an important part of modified starch. After organic acid treatment, such as malic, tartaric, citric, and glutaric acid, starch can be more widely used in various industries according to its different properties (Ačkar et al., 2015; Akubor, 2013; Barczynska et al., 2019; Lee et al., 2019). However, l ‐malic acid is easily prepared by microbial fermentation or enzymatic conversion which has stereospecificity, and can be used as a pasta enhancer (Battat et al., 1991; Iyyappan et al., 2019; Moon et al., 2008; Neufeid et al., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…From a nutritional aspect, starch can be classified into three categories based on digestibility: rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) [5][6][7]. RS is starch that is not digested in the small intestine (of healthy individuals), and might therefore be partially fermented by the gut microflora in the large intestine [5,[7][8][9]. At present, different methods have been applied to prepare RS, including chemical, physical (hydrothermal), and enzymatic modification methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…During these reactions, the hydroxyl group on the glucose ring in the starch chain reacts with the organic acid in order to form a cross-linked structure with a high content of resistant starch (RS) [12]. One of the acids, which, in recent articles, has been the most popular for the esterification procedure, is malic acid [2,4,5,7,12]. The predicted reaction of starch and malic acid is shown in Figure 1, and it is combined with a high temperature to improve the reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na et al (2021) reported the effect of malic acid treatment on various types of starch, determining that maize starch was the most effective substrate for increasing RS. Lee et al (2019) determined the optimum pH level to maximize the amount of RS when malic acid was used. However, there are no reports on the optimization of malic acid treatment using rice grains for RS formation.…”
Section: Introductionmentioning
confidence: 99%